EPID-21. THE NATIONAL SPECTRUM OF NEWLY-DIAGNOSED BRAIN TUMORS IN ADULT PATIENTS VARIES SIGNIFICANTLY BY PATIENT DEMOGRAPHICS. (11th November 2019) - Torre, Matthew; Ascha, Mustafa; Harary, Maya; Smith, Timothy; Aizer, Ayal; Ligon, Keith; Reardon, David; Barnholtz-Sloan, Jill; Iorgulescu, Bryan
Abstract: INTRODUCTION: Herein we examine the epidemiology and outcomes of the entire spectrum of intracranial tumors in the contemporary era. METHODS: Adult patients (≥20yo) presenting between 2010–2015 where the first evidence of cancer involves an intracranial tumor were queried from the National Cancer Database, which comprises >70% of cancers newly-diagnosed in the U.S. Tumor types were classified by WHO2016 ICD-O3, and stratified by patient characteristics. RESULTS: 361, 841 adults without a history of cancer presented with intracranial tumors between 2010–2015. Across all ages, these were comprised of 1) brain metastases (BMs; 25%: 29% in males vs. 23% in females); 2) meningiomas (25%: 15% in males, but 34% in females) including atypical (n=4, 565) and anaplastic (n=833); 3) diffuse infiltrative gliomas (21%: 26% in males vs. 17% in females), mostly GBMs (14%); followed by 4) sellar (14%), 5) cranial nerve (6%), and PCNSL (3%) tumors. The remaining types each comprised ≤2 % of brain tumors, including mesenchymal non-meningothelial tumors (2%), intracranial ependymal (0.8%), mixed neuronal-glial (0.7%), circumscribed "other astrocytomas" (0.6%, mostly pilocytic astrocytomas n=1, 307 and PXAs n=272), CNS embryonal (0.3%), pineal (0.2%), GCTs (0.1%), and choroid plexus (0.1%) tumors. In the 91, 686 patients presenting with a BM, the most common primaries were lung adenocarcinoma (39%), lung SmallCC (14%), lung SqCC (8%), breast (8% of females), melanoma (3%), kidney (3%), colorectal (2%), and esophageal (1%). The distributions of brain tumor types differed significantly by age, sex, race/ethnicity, and insurance status. CONCLUSIONS: In adult patients where the first manifestation of cancer includes an intracranial tumor, the most common diagnosis is either metastatic disease (predominantly from NSCLC) in males or benign meningiomas in females; but varies substantially by age group. Notably, our results adjust the traditional teaching that half of all new brain masses are BMs, which in fact represent only ~25% of new intracranial masses.